Farmer-led irrigation development has been boosted through value chain-based scaling partnerships established in four sub-Saharan African countries - CGIAR Research Program on Water, Land and Ecosystems (2021)
Scaling partnerships established by WLE/IWMI in Ghana and Ethiopia have substantially improved input and output market linkages along irrigated agricultural value chains. As a result, farmers have better access to irrigation technologies and services that can boost yields and incomes. Efforts are also under way in Ethiopia to link farmers to markets. Based on these results, a similar approach is being introduced in Mali and Zambia.